ANALISIS KANDUNGAN LOGAM TIMBAL (Pb) DAN CADMIUM (Cd) PADA TANAH PERKEBUNAN DAN TANAMAN JAMBU BIJI (Psidium Guajava) DI DESA PERAWANG BARAT KABUPATEN SIAK - Ardiansyah Hamid; Sofyan Husein Siregar; Sofia Anita (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2020)
Perawang Barat village is a village that produces guava. This can be seen from the number of guava plantations found along the Jalan Perawang Barat Village. The guava plant looks lush with large, dense fruit. To get good quality fruit, it is necessary to maximize virginity, such as fertilizing and spraying pesticides. For fertilization, manure and chemical fertilizers are used. Manure comes from chicken manure and chemical fertilizers consisting of KCL, ZA and TSP, while as many as nine types of pesticides are used for pesticides with different functions. Fertilizers and pesticides are sources of Pb and Cd metals. Continuous use of fertilizers and pesticides in the long term results in the accumulation of Pb and Cd metals in the soil. The metal content of Pb and Cd in the soil of 7.71 ppm and 0.37 ppm resulted in the contaminated category of plantation soil. For the distribution of Pb metal in guava plants, the highest Pb content was found in the leaves followed by the stems and roots. The high content of Pb metal in leaves can be caused by many factors, among others, Pb metal comes from the soil which is transferred by roots, the use of pesticides and airborne particulates from motor vehicle fumes.